2015
DOI: 10.1259/dmfr.20140189
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of CBCT for assessment of impacted mandibular third molars: a review – based on a hierarchical model of evidence

Abstract: A radiographic examination of mandibular third molars is meant to support the surgeon in establishing a treatment plan. For years panoramic (PAN) imaging has been the first choice method; however, where an overprojection is observed between the third molar and the mandibular canal and when specific signs suggest a close contact between the molar and the canal, CBCT may be indicated. The present review provides an evaluation of the efficacy of CBCT for assessment of mandibular third molars using a six-tiered hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 62 publications
(82 reference statements)
5
99
0
3
Order By: Relevance
“…A recently published review emphasizes this lack of relevant evidence. 17 Therefore, the actual GRADE categorization could be challenged claiming that the evidence level is "D" rather than "C". This means that there is little reliable knowledge concerning the consequences of pre-operative use of CBCT in the management of mandibular third molars, for neither the patients nor society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published review emphasizes this lack of relevant evidence. 17 Therefore, the actual GRADE categorization could be challenged claiming that the evidence level is "D" rather than "C". This means that there is little reliable knowledge concerning the consequences of pre-operative use of CBCT in the management of mandibular third molars, for neither the patients nor society.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this concept is anchored in scientific facts is not the subject of this study, but it seems that incitements for implementing new technology will tend to follow market rules and not entirely scientific or ethical standards. 17 There could be a discrepancy between the financial interests of the health provider and the society's demand for evidence-based practice. From the patient's point of view, the total price for surgical removal of a mandibular third molar in DK most probably will double if CBCT imaging becomes the routine.…”
Section: Discussionmentioning
confidence: 99%
“…Cone Beam imaging method named CBCT is based on a perfected computed tomography technology applicable throughout the dentistry area. [7] In maxillo-facial osseous conditions, CBCT provides information on the precise location of various pathological processes developed in the jaws or facial soft tissues and data about the adjacent anatomical structures. [8] The presence of certain radiological signs on panoramic radiography such as narrowing, darkening or deflection of the root, dark, bifid or island-shaped apex, interruption of the mandibular canal cortical contour, canal deflection or narrowing, are associated with a veritable relationship between the roots of the third molar and the mandibular canal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it could help to select the adequate surgical technique and to establish the foundation of the patient's informed consent. Sensory disturbances in the innervation area of the IAN have been reported to vary between 0.4% and 6% 2 and constitute a serious complication.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, a review on radiographic examination of mandibular third molars reported that there is little evidence that CBCT will change either the treatment or the post-operative patient outcome. 2 Moreover, it has been documented that the use of CBCT is connected with higher costs and radiation to the patient than conventional methods. [4][5][6][7][8] Currently, no exact protocol of the radiographic examination of mandibular third molars exists, and therefore no strict guidelines for general practitioners (GPs) to follow have been advocated.…”
Section: Introductionmentioning
confidence: 99%